The mindful diet : how to transform your relationship with food for lasting weight loss and vibrant health - Wolever, Ruth; Reardon, Beth; Hannan, Tania (Scribner, 2015)
Addresses the unhealthy behaviors that derail most diets and provides a science-based approach to eating mindfully to stop cravings, end emotional overeating, and have lasting weight loss and health.